Faktor Penggunaan E-Commerce dalam Meningkatan Kinerja Usaha Travel di Kabupaten Pangkep - Tenriyola, Andi Putri; Nurwafiyyah, Auliyah; Mas'ud, Anis Anshari (Universitas Sulawesi Barat, 2023)
The travel industry has experienced rapid development due to the utilization of e-commerce, and marketing technologies such as e-commerce serve as tools in managing business resources. Therefore, this research aims to examine the factors influencing the use of e-commerce in enhancing the performance of travel businesses. This study adopts an explanatory research approach, intending to elucidate the relationships between various variables through hypothesis testing. The unit of analysis in this research is businesses in the Pangkep Regency, South Sulawesi, specifically those engaged in travel ticketing services. The research findings reveal three main factors affecting the use of e-commerce for business performance improvement: integrated information systems, networking, and technological innovation. Additionally, this study is supported by the Technology Organization Environment (TOE) theory to assess companies' decisions in adopting new technologies such as e-commerce. The research findings contribute to enhancing the understanding of travel industry practitioners in utilizing e-commerce technology